Neural reservoir control of a bio-hybrid soft arm - Noel Naughton; Arman Tekinalp; Keshav Shivam; Seung Hyun Kim; Apoorva Khairnar; Volodymyr Kindratenko; Mattia Gazzola (Proceedings of the National Academy of Sciences, 2026)
A long-standing engineering problem, the control of soft robots is difficult because of their highly nonlinear, heterogeneous, anisotropic, and distributed nature. Here, bridging engineering and biology, neural reservoirs are employed for the dynamic control of a bio-hybrid model arm made of multiple muscle-tendon groups enveloping an elastic spine. We show how the use of reservoirs facilitates simultaneous control and self-modeling across challenging tasks, outperforming classic neural network approaches. Further, through the use of spiking reservoirs on neuromorphic hardware, energy efficiency gains of up to 75 and 45 times are obtained relative to standard and high-efficiency CPUs, with implications for the on-board control of untethered, small-scale systems.